Study of Policy Implementation on Placement, Protection of Migrant Worker From Against the Transmission of HIV-AIDS - Nofriana Inna Manulangga; David B. W. Pandie; Frans Salesman; Anderias Umbu Roga; Muntasir Muntasir (Jurnal Health Sains, 2023)
Used Edward III's policy theory, this study aims to analyze Communication (X1), Resources (X2), Bureaucracy (X3), and Disposition (X4) affect the performance of public policy implementation in the placement and protection of Indonesian Migrant Workers from NTT impact on the transmission of sexually transmitted infections HIV AIDS in NTT (Y). Conducted in Kupang City by taking PPTKIS Citra Bina Tenaga Kerja (CBTM) as a recruiting, training and sending agent. Respondents were 93 people from 122 populations, who departed in 2016-2017 and returned in 2019-2020. Research sample is purposive and snowball sampling. The results show that implementation performance (Y) has not gone well. Statistical analysis used SPSS 26: 1) X1 has a parameter coefficient (original Sample 0.280) against (Y), where the effect was positive and significant (t = 2.946>t-table 1.662); 2) X2 has a parameter coefficient (original sample -0.153) against (Y), where the effect was positive and significant (t = -1.629<t-table 1.662 ); 3) X3 has a parameter coefficient (original sample 0.052) against (Y), where the effect was positive and significant (t = 1.001 <t-table 1.662); 4) X4 has the lowest parameter coefficient (original sample 0.116) (Y), where the effect was positive and significant (t = 2.267>t-table 1.662). The strongest variable influencing policy implementation is communication.